Formation of multicultural competence of preschool children - Rudnytska-Yuriichuk, Iryna; Kurhannikova, Olha; Demchenko, Olena; Tolchieva, Hanna; Holiuk, Oksana (Revista Tempos e Espaços em Educação, 2022)
The peculiarities of the development of the modern globalized world indicate the need to address the field of culture as an important principle of raising children from preschool age. The purpose of the article is to analyze the formation of the foundations of multicultural competence of preschool children in Ukraine. The objectives of the study are: to investigate the features of the theoretical perception of multiculturalism in the modernUkrainian pedagogical system, to interpret empirical material on the attitude to multiculturalism among the surveyed parents and preschool children. The research is based on the use of theoretical research methods, including analysis, synthesis, inductionand deduction, concretization, comparison, abstraction. Also, the study was formed as a result of using a statistical method, which consisted of qualitative analysis of experimental data. The results show that the multicultural development environment is an integrated category, which includes various areas of activity of the preschooler, so it is important to provide special conditions, a stable psychological atmosphere. The work on the basis of empirical material summarizes the favorable attitude of preschool children to foreigners and the desire of parents to deepen this program. According to our author's definition, multicultural education should be understood as the process of assimilation by preschoolers of values and experiences of other ethnic groupsin the region where they live, with special emphasis on the study of their cultural achievements and national characteristics.
Formação de competência multicultural de crianças pré-escolares
Keywords: Analysis. Education system. Tolerance